2016
DOI: 10.1177/1060028016648367
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Versus Methadone for Opioid Dependence in Pregnancy

Abstract: Both methadone and buprenorphine are effective agents, with improved safety compared with continued nonmedical opioid use during pregnancy. There is evidence to suggest that buprenorphine should be considered as an equivalent option to methadone for use in pregnancy; however, larger studies are still needed to fully evaluate buprenorphine safety and advantages over methadone in the obstetric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…13 While ED studies have often excluded pregnant patients, research outside of emergency settings has shown that buprenorphine is safe and effective for pregnant patients. 28 Few studies examined additional clinical factors associated with improved treatment outcomes. Two cohort studies reported on factors associated with a decreased likelihood of remaining in treatment.…”
Section: Identification Of Patients For Inductionmentioning
confidence: 99%
“…13 While ED studies have often excluded pregnant patients, research outside of emergency settings has shown that buprenorphine is safe and effective for pregnant patients. 28 Few studies examined additional clinical factors associated with improved treatment outcomes. Two cohort studies reported on factors associated with a decreased likelihood of remaining in treatment.…”
Section: Identification Of Patients For Inductionmentioning
confidence: 99%
“…There was no significant interaction between maternal maintenance treatment, gestational age and the likelihood of the baby receiving treatment for NAS, but only a small proportion of mothers in Gibson's study had been maintained on buprenorphine, and so there may be a type II error. Less severe NAS has been described by others for babies born to buprenorphine, compared to methadone-maintained mothers [9,10].…”
mentioning
confidence: 59%
“…There was no significant interaction between maternal maintenance treatment, gestational age and the likelihood of the baby receiving treatment for NAS, but only a small proportion of mothers in Gibson's study had been maintained on buprenorphine, and so there may be a type II error. Less severe NAS has been described by others for babies born to buprenorphine, compared to methadone-maintained mothers [9,10].Opioid withdrawal in the newborn is a complex and incompletely understood process with considerable longer-term effects. Increasing evidence points to adverse effects of opioid exposure upon the developing brain, with disproportionately small head circumference at birth and abnormal cortical visual evoked potentials [11][12][13].…”
mentioning
confidence: 92%
“…Although unknown whether clinically significant, these characteristics of fetal physiology are indicative of positive fetal health 58. Other studies have also demonstrated an increase in fetal activity and heart rate variability,59 higher average gestational ages at birth, and higher average birth weights with buprenorphine treatment compared to methadone 60,61…”
Section: Treatment Options and Decisionsmentioning
confidence: 98%